Reinforcing character education through islamic religious education pedagogy for elementary school students in the digital era - Dian Komalasari; Iche Mionarti; Meri Hartati; Meilisa Sajdah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The digital era has significantly influenced elementary school students’ behavior, values, and religious practices. Increased exposure to digital technology presents both opportunities and risks, including moral decline, individualism, and weakened religious and social values. In this context, Islamic Religious Education (PAI) plays a strategic role in strengthening students’ character formation. This study employed a descriptive qualitative approach. Data were collected through a literature review, semi-structured interviews with PAI teachers, and classroom observations conducted in several Islamic elementary schools. The data focused on learning practices, character value integration, and challenges in implementing PAI in the digital environment. The findings indicate that PAI effectively fosters key character values such as honesty, discipline, responsibility, and tolerance when delivered through contextual and innovative learning strategies. PAI teachers function not only as instructors but also as moral role models, spiritual facilitators, and emotional mentors. However, major challenges include limited digital literacy among teachers, insufficient parental supervision of students’ media use, and weak coordination between schools and families.The effectiveness of character education through PAI in the digital age depends on strong collaboration among schools, families, and communities, as well as the responsible use of technology. This study recommends enhancing teachers’ digital competencies, developing Islamic-based digital learning content, and strengthening the role of families as primary agents of character education.